Challenging organized crime in the western hemisphere : a game of moves and countermoves - Heymann, Philip B.; Heymann, Stephen P.; Taylor and Francis (Boca Raton, FL : Routledge, an imprint of Taylor and Francis, 2018)
Challenging Organized Crime in the Western Hemisphere: A Game of Moves and Countermoves takes the unusual approach of exploring and describing how organized crime groups develop their capacities in response to heightened powers of law enforcement; and how law enforcement in turn responds, creating an ongoing dynamic interaction. The book shows how a state, such as the United States, has and can develop new laws and practices in ways that enable them to deal with relatively large violent groups and yet preserve the rule of law and civil liberties.This thought- provoking book is ideal for students of organized and transnational crime in university programs and law schools, as well as researchers and legal practitioners, who seek to look beyond the simple traditional history of organized crime and develop a strategy to confront organized crime in the future.While most texts describe organized crime groups and the challenges to government they impose from a static perspective, the authors dissect the interaction over time of organized crime and democratic governance that has created the present structure and balance of advantages in the United States. Readers learn about the markets for contraband and extortionate protection that form the bulk of organized criminal enterprise, the vulnerabilities of the traditional practices and rules of law enforcement, the effects of globalization of criminal enterprises on their contest with the state, the effectiveness of various practices of law enforcement, and the continuing forces of change, often technological, in the businesses of organized crime and law enforcement that play important roles in the contest between them.
part PART ONE The Business of Organized Crime (OC): The Concerns of States -- chapter 1 What is Organized Crime? -- chapter 2 The Sinaloa Cartel as a Concrete Example -- chapter 3 Strategies for a State Addressing Organized Crime -- chapter 4 A Final Issue of State Strategy: Rules of War or Law Enforcement -- chapter 5 Detecting Visible Indications of Organized Crime -- part Part Two Law Enforcement on Steroids -- chapter 6 The Mechanisms and Difficulties of Traditional Law Enforcement in Addressing Organized Crime -- chapter 7 Creating a Law Enforcement Capacity to Address the Advantages of Organized Crime -- chapter 8 New Strategies for Prosecutors of Organized Crime -- chapter 9 A Double- Edged Sword: How Improved Law Enforcement Aided Whitey Bulger -- part Part Three Globalization -- chapter 10 Going International -- chapter 11 International Law Enforcement Cooperation Pursuant to Treaties -- chapter 12 The Colombian Connection: A Truly Cooperative Solution for an International Problem -- chapter 13 Two Critical Ingredients of International Cooperation -- part Part Four Moving the Proceeds of Organized Crime in Secret -- chapter 14 Moving Proceeds of Crime Without Revealing their History -- chapter 15 The Limited Effectiveness of a Barrage of Prohibitions of Money Laundering -- part Part Five The Future of Organized Crime -- chapter 16 The Internet and the Exploitation of the Fog of War -- chapter 17 Conclusion: Predicting the Future of the Contest Between Nations and Sizable Criminal Enterprises.
Keywords: SOCIAL SCIENCE / Criminology; Organized crime; Transnational crime